Resonant Micromachined magnetic field sensor - Zaidatul Asikin Abd Muhed (Universiti Malaysia Perlis, 2008)
This project is about the development of a micromachined magnetic field sensor. The operation of this sensor is based on a shift of the resonant frequency of a resonating microstructure in presence of a magnetic field. The flexural beams of the micromachined resonator are designed so that an axial force is exerted on them when exposed to a magnetic field. The axial force will cause a positive or negative shift in the resonant frequency of the structure depending on the directions of the magnetic field and DC current flows in the crossbars of the sensor. The electric field of this sensor can be determined by using the thermal analysis. Magnetic field sensing has vastly expanded as industry has adapted a variety of magnetic sensors to detect the presence, strength, or direction of magnetic fields not only from the earth, but also from permanent magnets, magnetized soft magnets, vehicle disturbances, brain wave activity, and fields generated from electric currents. Magnetic sensors can measure these properties without physical contact and have become the eyes of many industrial and navigation control systems.